Short communication: A laboratory study to validate the impact of the addition of Alnus nepalensis leaf litter on carbon and nutrients mineralization in soil - GAURAV MISHRA; KRISHNA GIRI; ANTARA DUTTA; SATABDI HAZARIKA; PRATUL BROGOHAIN (Nusantara Bioscience, 2016)
Abstract. Mishra G, Giri K, Dutta A, Hazarika S, Borgohain P. 2016. A laboratory study to validate the impact of the addition of Alnus nepalensis leaf litter on carbon and nutrients mineralization in soil. Nusantara Bioscience 8: 5-7. Plant litter or residues can be used as soil amendment to maintain the carbon stock and soil fertility. The amount and rate of mineralization depend on biochemical composition of plant litter. Alnus nepalensis (Alder) is known for its symbiotic nitrogen fixation and capability to restore fertility of degraded lands. A laboratory incubation experiment was conducted for 60 days under controlled conditions to validate the carbon and nutrients mineralization potential of alder litter. Soil fertility indicators, i.e. soil organic carbon (SOC), available nitrogen (N), available phosphorus (P), and available potassium (K) were analyzed using standard procedures. Significant differences were observed in the soil properties after addition of litter. Nutrient composition of alder litter was found superior by providing significantly higher organic matter and helped in better nutrient cycling. Therefore, alder based land use system may be replicated in other degraded lands or areas for productivity enhancement which is important for sustaining biodiversity and soil fertility.